Colored Text Enhances Learning Power of Medical Students “A New Concept of Learning” (Medical Forum Monthly, 2024)
Objectives: To assess colored text motivates, enhances concentration & learning Skills of medical students. To assess colored text helps in memory retention & release stress, anxiety of medical studentsStudy Design: A Cross Sectional StudyPlace and Duration of Study: This study was carried out among the medical students of Sindh & Dow medical College, Karachi from March to December 2010,Materials and Methods: A sample 341 student was drawn through systemic random sampling. Every 5th student was selected, ischiaria chart was used for color blindness and Students were divided into 2 groups. One group was given paragraph with important points written in bold black, second group with important points written in different colored. Data was collected through structured questionnaire, entered & analyzed on SPSS version 16.Results: Out of 341 students, 83.60% students were motivated by colored text, 80.90% students maintained interest, 74.80% student’s maintained concentration, 77.10% students had memory retention and 53.1% student had released their stress and anxiety. Overall 84.80% students preferred colored text over black and white text.Conclusion: The study proved significant difference between the two groups, students with colored text showed good memory retention, motivation, concentration, Stress was also relieved by colored text.